2006
DOI: 10.2174/156802606776894465
|View full text |Cite
|
Sign up to set email alerts
|

Glycine/NMDA Receptor Antagonists as Potential CNS Therapeutic Agents: ACEA-1021 and Related Compounds

Abstract: Glutamate is the main excitatory neurotransmitter in central nervous system (CNS) and NMDA receptors are one of the major classes of ionotropic glutamate receptors. NMDA receptors have been known to play critical roles in normal CNS activities, as well as in many pathological conditions, including both acute and chronic diseases. The discovery of glycine as a coagonist of NMDA receptors has led to intensive research of glycine/NMDA antagonists as potential CNS drugs. The robust efficacy of glycine/NMDA antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…These second-generation memantine-derivative therapeutics were designed to be activated under pathologically conditions and, in preliminary studies, appear to offer better neuroprotection [17 ]. Traxoprodil (CP-101606) antagonist is highly selective for the NR2B subunit of the NMDA receptor [18]; ACEA-1416, an analog of ACEA-1021 [19], and arcaine, an analog of agmatine [20], have been shown to be neuroprotective in animal models of brain injury and ischemia, and appear to better tolerated. a-Amino-3-hydroxy-methyl-4-isoxazolylpropionic acid receptor antagonists…”
Section: N-methyl-d-aspartic Acid Receptor Antagonistsmentioning
confidence: 99%
“…These second-generation memantine-derivative therapeutics were designed to be activated under pathologically conditions and, in preliminary studies, appear to offer better neuroprotection [17 ]. Traxoprodil (CP-101606) antagonist is highly selective for the NR2B subunit of the NMDA receptor [18]; ACEA-1416, an analog of ACEA-1021 [19], and arcaine, an analog of agmatine [20], have been shown to be neuroprotective in animal models of brain injury and ischemia, and appear to better tolerated. a-Amino-3-hydroxy-methyl-4-isoxazolylpropionic acid receptor antagonists…”
Section: N-methyl-d-aspartic Acid Receptor Antagonistsmentioning
confidence: 99%
“…Excess release of glutamate from presynaptic membranes induced by ischemia overactivates glutamate receptors leading to a series of events including intracellular calcium overload, excessive ROS production and mitochondrial stress and finally neuronal death (Benveniste et al, 1984 ; Lipton and Rosenberg, 1994 ). However, based on accumulating evidence in the literature, all clinical trials using glutamate receptor inhibitors have failed (Koh and Choi, 1991 ; Morris et al, 1999 ; Albers et al, 2001 ; Ikonomidou and Turski, 2002 ) although some of the inhibitors reduced ischemic damage in animal experiments (Lin et al, 1993 ; Reyes et al, 1998 ; Cai, 2006 ). It is known that glutamate receptors play important roles in maintaining physiological functions such as excitatory signal transduction, learning and memory (Mayer and Westbrook, 1987 ; Newcomer et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of various subunits and their combinations, glycine can bind to GluN1 and GluN3 subunits1112 with pharmacological and structural differences in both binding sites1314. More importantly, it has been suggested that the glycine binding site of GluN1 is a potential pharmacological target for treating PD, schizophrenia, traumatic brain injury, and anxiety15161718.…”
mentioning
confidence: 99%